"An Unlikely Collection of Union Militants": Portuguese Immigrant Cleaning Women Become Political Subjects in Postwar Toronto - Miranda, Susana (Atlantis, 2007)
This paper examines the ways in which Portuguese immigrant women office cleaners gained a public presence during a six-week strike in 1984, both on the picket lines and in Toronto's newspapers. Their ethnic, gender, and class identities were central in their transformation into public, political, and militant subjects.